A new displacement bound technique for rigid plastic continua subjected to strong dynamic loading at large deflections - The, Vu Van; Tinh, Tran Ba (Vietnam Journal of Mechanics, 1987)
A new displacement bound technique, which is based on concept of admissible fields has been developed for rigid Plastic continua subjected to strong dynamic loading at large deflections, the lower hound obtained (2.11) depends on kinematic ally admissible displacement  ui and kinematic ally admissible velocity ui* which must be chosen so that the condition (2.14) may be satiafidc. Parameter T* would be determinated by maximizing the right hand side of (2.11).